Impact of Macroeconomic Movements on Changes in Stock Returns - Sugiyanto Ikhsan; Dodi Sukmayana; Laely Purnamasari (Universitas Pendidikan Ganesha, 2022)
In the macroeconomic context, the impact of inflation will be felt by all companies in the industry. This condition will affect the performance of the capital market because many companies cannot operate optimally. As a result, the capital market faces high uncertainty. The problem of timeliness in buying or selling shares often makes investors experience losses in investing. This condition indicates that there is a need for an academic study that is able to predict the factors that influence stock returns. This study aims to examine the effects of inflation, exchange rates, and interest rates on stock returns. This study uses a quantitative approach with a causal paradigm. The population in this study is macroeconomic data and stock returns of the Composite Stock Price Index (JCI) during the 2009–2020 period. Data analysis used regression with the classical assumption tests previously carried out, namely normality, autocorrelation, multicollinearity, heteroscedasticity, and linearity tests. The data test program used is eviews-10. The findings revealed that macroeconomics affect stock returns simultaneously; inflation has a negative effect on stock returns; interest rates and exchange rates have a positive effect on stock returns. The results of this study indicate a conformity with the Arbitration Pricing Theory (APT), which states that asset pricing can be predicted by examining macroeconomic factors.